Effect of yeast strains on the chemical composition of ciders from Finnish apple cultivars - Okwum, Ada (My University, 2024)
Effect of Saccharomyces and non- Saccharomyces yeast in apple ciders and juices were studied using Gas chromatography fitted with Flame Ionization Detector. Samples were produced from six different Finnish apple cultivars using two different commercial yeasts strains Saccharomyces cerevisiae and Torulaspora delbrueckii. Apple juice samples was inoculated with yeast and fermented at 22°C for 30 days. The results showed no notable difference among the ciders obtained. Ethanol content was similar (4.1-8.0 %v/v) SE compared to TD (3.3 -7.6 %v/v). Furthermore, the apple cultivars were significantly different in their sugar (sucrose, fructose, glucose, and sorbitol) contents, Malic, and ascorbic acids compositions. Additionally, a decrease in malic acid among the alcoholic juices was observed with those from TD fermentation slightly higher than SE. Also changes in qunic acid and ascorbic acid content was not detected in both yeast fermentation except in ‘Tu1’ sample with SE and ‘Ra’ sample fermented with TD. Both yeasts consumed fructose, glucose, and sucrose completely during fermentation. Sorbitol an alcoholic sugar was found similar in ‘Antonovka’ and ‘Tunista2’ samples and slightly different in ‘Alkesanter’, ‘Musti-Iso Venalainen’, ‘Tunista2’ and ‘Rambo’ fermented juices samples with T. delbrueckii yeast. Citric acid was found present in all apple juice sample but not detected in ‘Al’ cultivar. Additionally, ascorbic and quinic acids was identified in all apple juice samples however in low quantity. The results illustrate effect was dependent on cultivar and not yeast strains. ‘Rambo’ cultivar differed from others producing more juice with low malic acid content, highest ethanol (7.8 -8.0% v/v) and total sugar cider and juice. Therefore, ‘Rambo’ cultivar was identified as suitable for cider production with Saccharomyces cerevisiae or Torulaspora delbrueckii however further studies should focus on the phenolic compounds and sensory perception of ‘Ra’ in comparison to other cultivars. Also, sequential fermentation with both yeast and other non- Saccharomyces yeast like should be considered to produce higher quality alcoholic beverages.
Keywords: fermentation, inoculation, apple cider, yeast, cultivars, malic acid.